Characterisation of Byzantine and early Islamic primary tank furnace glass. (August 2018) - Brems, Dieter; Freestone, Ian C.; Gorin-Rosen, Yael; Scott, Rebecca; Devulder, Veerle; Vanhaecke, Frank; Degryse, Patrick
Abstract: In order to improve the understanding of glass production and provenance, we present trace element and Sr, Nd and B isotope ratio data for 15 samples of raw natron glass from a single tank furnace in Apollonia (6th–7th century CE) and eight glass samples from two tank furnaces in Bet Eli'ezer (8th century CE) in Israel. This data provides information about the geochemical homogeneity within a single batch of raw glass and about the differences and/or similarities between different tank furnaces on a single site. Four glasses from a secondary workshop at Tell el-Ashmunein, Egypt (8th–9th century CE) are analysed for comparative purposes. All raw glass samples have uniform trace element patterns and ratios. Because of poor mixing of the glass batch before and during firing, absolute concentrations however can vary significantly within a single tank furnace. The concentrations of trace elements commonly associated with (de)colouring are very low and can be attributed to background concentrations in the sand raw materials. This indicates that there was no obvious recycling of glass cullet at this stage of the production process and that the tank furnace glass is primary glass in the true sense of the word. The isotopic compositions of Sr, Nd and B in the tank furnace glasses are relatively homogeneous. This confirms their potential as provenance indicators. The isotopic composition of Sr in tank furnace glass from Apollonia and Bet Eli'ezer indicates that the lime was derived from seashell, suggesting the glass was produced from beach sand. Glass from Tell el-Ashmunein contains Sr with lower 87 Sr/ 86 Sr ratios, pointing to the use of limestone as the source of lime. All primary glasses from Israel analysed have Nd isotopic compositions typical for an Eastern Mediterranean origin. δ 11 B indicates that natron used in the tank furnaces in Apollonia and Bet Eli'ezer was most likely imported from Egypt. Highlights: Trace element and Sr, Nd and B isotopic characterisation of primary tank furnace glass Provenancing raw materials used in the production of primary glass Geochemical homogeneity within a single batch of raw glass Differences and similarities between tank furnace glass on a single site